2021
DOI: 10.1101/2021.02.21.432154
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Transient Metabolic State In Melanoma Persister Cells Mediated By Chemotherapeutic Treatments

Abstract: Persister cells are defined as the small fraction of quiescent cells in a bulk cancer cell population that can tolerate unusually high levels of drugs. Persistence is a transient state that poses an important health concern in cancer therapy. The mechanisms associated with persister phenotypes are highly diverse and complex, and many aspects of persister cell physiology remain to be explored. We applied a melanoma cell line and panel of chemotherapeutic agents to show that melanoma persister cells are not nece… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…We first treated A375 cells with different concentrations of VEM for 3 days to generate a kill curve (survival ratio vs. VEM concentration) (Figure 1a). The data show that the half maximal inhibitory concentration (IC 50 ) of VEM for A375 cells was ~100 nM and a treatment concentration higher than 10 × IC 50 did not significantly affect the persister ratio (i.e., cell survival ratio) [17]. As persisters survive high concentrations of drugs, persister cells were isolated by treating A375 cells with VEM at 100 × IC 50 concentration for 3 days, consistent with previous studies [17,19,20].…”
Section: Vemurafenib Persister Cells Are Slow-cycling Cells That Are Reversibly Drug Tolerantsupporting
confidence: 86%
See 2 more Smart Citations
“…We first treated A375 cells with different concentrations of VEM for 3 days to generate a kill curve (survival ratio vs. VEM concentration) (Figure 1a). The data show that the half maximal inhibitory concentration (IC 50 ) of VEM for A375 cells was ~100 nM and a treatment concentration higher than 10 × IC 50 did not significantly affect the persister ratio (i.e., cell survival ratio) [17]. As persisters survive high concentrations of drugs, persister cells were isolated by treating A375 cells with VEM at 100 × IC 50 concentration for 3 days, consistent with previous studies [17,19,20].…”
Section: Vemurafenib Persister Cells Are Slow-cycling Cells That Are Reversibly Drug Tolerantsupporting
confidence: 86%
“…The data show that the half maximal inhibitory concentration (IC 50 ) of VEM for A375 cells was ~100 nM and a treatment concentration higher than 10 × IC 50 did not significantly affect the persister ratio (i.e., cell survival ratio) [17]. As persisters survive high concentrations of drugs, persister cells were isolated by treating A375 cells with VEM at 100 × IC 50 concentration for 3 days, consistent with previous studies [17,19,20]. After treatment, the cells were cultured in a fresh, drug-free growth medium for 24 h to remove dead/apoptotic cells.…”
Section: Vemurafenib Persister Cells Are Slow-cycling Cells That Are Reversibly Drug Tolerantmentioning
confidence: 95%
See 1 more Smart Citation
“…While shorter duration of BRAF and RAF/MEK inhibition gives rise to NCSC phenotype (NGFR+ cells), prolonged exposure facilitates undifferentiated cells ( Fallahi-Sichani et al., 2017 ; Su et al., 2017 ). How does adaptation at different time scales contribute to emergence and maintenance of drug-tolerant persisters ( Shaffer et al., 2017 ; Ahmed and Haass, 2018 ; Schuh et al., 2020 ), and the role of reversible cellular reprogramming ( Roesch et al., 2010 ; Karki et al., 2021 ) in enabling such persisters requires further careful investigation. Understanding the dynamics and trajectories of phenotypic switching in these scenarios can help guide better combinatorial ( Boshuizen et al., 2018 ; Luo et al., 2018 ) and/or sequential ( Goldman et al., 2015 ) therapies that can target vulnerabilities of diverse phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…DTPs adapt to environmental fluctuations through epigenomic, transcriptional and metabolic reprogramming events, and are capable of expanding into a colony (Shen et al, 2020b). Initially reported in lung cancer (Sharma et al, 2010), persisters have been reported in other cancer types as well such as melanoma and colorectal cancer (Hangauer et al, 2017;Karki et al, 2021;Mikubo et al, 2021;Oren et al, 2021;Rehman et al, 2021;Shen et al, 2020a). Intriguingly, DTPs can act as a reservoir subpopulation through which genetically mutated cells can emerge to stabilize diverse drug-resistance mechanisms at a longer time-scale (Ramirez et al, 2016).…”
Section: Are Mutations Necessary For Cancer Progression?mentioning
confidence: 99%